DNA interstrand cross-links of the novel antitumor trinuclear platinum complex BBR3464. Conformation, recognition by high mobility group domain proteins, and nucleotide excision repair - Kasparkova, Jana; Zehnulova, Jana; Farrell, Nicholas; Brabec, Viktor (The Journal of biological chemistry, 2002)
The novel phase II antitumor polynuclear platinum drug BBR3464 ([(trans-PtCl(NH(3))(2))(2)(mu-trans-Pt(NH(3))(2)(NH(2)(CH(2))(6)NH(2))(2))](NO(3))(4)) forms intra- and interstrand cross-links (CLs) on DNA (which is the pharmacological target of platinum drugs). We examined first in our recent work how various intrastrand CLs of BBR3464 affect the conformation of DNA and its recognition by cellular components (Zehnulova, J., Kasparkova, J., Farrell, N., and Brabec, V. (2001) J. Biol. Chem. 276, 22191-22199). In the present work, we have extended the studies on the DNA interstrand CLs of this drug. The results have revealed that the interstrand CLs are preferentially formed between guanine residues separated by 2 base pairs in both the 3' --> 3' and 5' --> 5' directions. The major 1,4-interstrand CLs distort DNA, inducing a directional bending of the helix axis and local unwinding of the duplex. Although such distortions represent a potential structural motif for recognition by high mobility group proteins, these proteins do not recognize 1,4-interstrand CLs of BBR3464. On the other hand, in contrast to intrastrand adducts of BBR3464, 1,4-interstrand CLs are not removed from DNA by nucleotide excision repair. It has been suggested that interstrand CLs of BBR3464 could persist considerably longer in cells compared with intrastrand adducts, which would potentiate the toxicity of the interstrand lesions to tumors sensitive to this polynuclear drug.
Keywords: molekulární konformace; DNA primery; DNA; proteiny s vysokou pohyblivostí; DNA Repair; poškození DNA; sekvence nukleotidů; oprava DNA; Base Sequence; Molecular Conformation; Organoplatinum Compounds; protinádorové látky; organoplatinové sloučeniny; DNA Damage; DNA Primers; High Mobility Group Proteins; Antineoplastic Agents